2016
DOI: 10.18632/oncotarget.12684
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-7 inhibits cell proliferation, migration and invasion in human non-small cell lung cancer cells by targeting FAK through ERK/MAPK signaling pathway

Abstract: ObjectiveTo investigate the effects of microRNA-7 (miR-7) on the proliferation, migration and invasion of non-small cell lung cancer NSCLC) cells by targeting FAK through ERK/MAPK signaling pathway.MethodsNSCLC tissues and adjacent normal tissues were obtained from 160 NSCLC patients after operation. NSCLC cell lines (A549, H1299 and H1355) and a normal human fetal lung fibroblast cell line (MRC-5) were obtained. NSCLC cells were assigned into miR-7 inhibitors, miR-7 mimics, blank, miR-7 mimics control, miR-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 33 publications
4
52
0
Order By: Relevance
“…In addition, the Erk signaling pathway has been shown to be frequently activated in numerous kinds of human cancers [43][44][45]. Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47]. Recent reports point out that miR-379 acts as a tumor [45], miR-7 inhibits the activation of ERK/MAPK signaling pathway by down-regulating FAK expression [46], and miR-622 overexpression decreases invasion in lung tumor cells by inhibiting HIF-1alpha via inactivation of ERK signaling in A549 cell [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Erk signaling pathway has been shown to be frequently activated in numerous kinds of human cancers [43][44][45]. Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47]. Recent reports point out that miR-379 acts as a tumor [45], miR-7 inhibits the activation of ERK/MAPK signaling pathway by down-regulating FAK expression [46], and miR-622 overexpression decreases invasion in lung tumor cells by inhibiting HIF-1alpha via inactivation of ERK signaling in A549 cell [47].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47]. Recent reports point out that miR-379 acts as a tumor [45], miR-7 inhibits the activation of ERK/MAPK signaling pathway by down-regulating FAK expression [46], and miR-622 overexpression decreases invasion in lung tumor cells by inhibiting HIF-1alpha via inactivation of ERK signaling in A549 cell [47]. Consistent with these findings, we found that the p-Erk level was significantly decreased in response to GCNT3 silencing or miR-302b-3p overexpression in XWLC and NCI-H292 cells, suggesting that the effect of the miR-302b-3p/GCNT3 signaling pathway in NSCLC may depend on the activation of p-Erk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, miR‐7 also participated in the pathogenesis that initiated the development of assorted disorders through acting on the downstream pathways. To be specific, miR‐7 could affect proliferation and migration of NSCLC cells by modulation of ERK/MAPK signalling or mediation of TLR9 signalling 16, 17. The miR‐7/NF‐κB signalling axis also mattered for its modulating the metastatic conditions of gastric cancer cells, so this axis might also be responsible for the aetiology of additional cancers, such as NSCLC 18, 19, 20.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao’ et al showed that miR-7 enhances cytotoxicity induced by gefitinib in NSCLC via inhibiting the EGFR and IGF1R signalling pathways [10]. Also, it was reported that miR-7 inhibits cell proliferation, migration and invasion in human non-small cell lung cancer cells by targeting FAK through ERK/MAPK signaling pathway [11]. However, the clinicopathological and prognostic significance of miR-7 in human LA and its roles in regulation of CDDP resistance of LA cells are unclear.…”
Section: Introductionmentioning
confidence: 99%